PENGARUH VARIABEL MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM PADA JAKARTA ISLAMIC INDEX 70 - Mufid, Asep Kholidul; Rosyidah, Norma (Journal of Financial Economics & Investment, 2024)
Macroeconomic variables such as inflation, exchange rates, money supply and Gross Domestic Product continue to fluctuate in each period, so they are indicated to have an influence on activities that occur in the Indonesian capital market. This research aims to analyze the influence of inflation, exchange rate, money supply and Gross Domestic Product on the Jakarta Islamic Index 70 (JJI70)' stock price index. The data used in this research is quarterly secondary data from 2018 to 2022. The analytical method used is multiple linear regression analysis. The research results show that inflation, the exchange rate and the money supply have a significant effect on the JJI70 stock price index, while the Gross Domestic Product variable does not have a significant effect on the JJI70 stock price index.